2001
DOI: 10.1097/00006123-200111000-00026
|View full text |Cite
|
Sign up to set email alerts
|

The Camino Intracranial Pressure Sensor: Is it Optimal Technology? An Internal Audit with a Review of Current Intracranial Pressure Monitoring Technologies

Abstract: The Camino ICP sensor remains one of the most popular ICP monitoring devices for use in patients with traumatic brain injuries. However, our recent in-house assessment demonstrated the robustness of the device to be less than adequate during routine practice. In this study, more than 50% exhibited zero drift greater than 3 mmHg, which is unacceptable in a catheter tip ICP monitoring device in which zero drift and calibration cannot be checked in vivo. A review of the literature revealed that other available IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 16 publications
1
33
0
3
Order By: Relevance
“…Technical errors were present in 4,5% of cases, most often related to the fiber optic cable itself. Similar study by Piper et al [75] found 10% faulty sensors in a study that included a total of 50 Camino monitors. Another study [76], in which 328 patients with a Camino monitor were examined, showed hemorrhage in 1,1% of cases, infection, in 4,75% and technical errors in 3,14%.…”
Section: Invasive Methods Of Measuring Icpsupporting
confidence: 71%
See 1 more Smart Citation
“…Technical errors were present in 4,5% of cases, most often related to the fiber optic cable itself. Similar study by Piper et al [75] found 10% faulty sensors in a study that included a total of 50 Camino monitors. Another study [76], in which 328 patients with a Camino monitor were examined, showed hemorrhage in 1,1% of cases, infection, in 4,75% and technical errors in 3,14%.…”
Section: Invasive Methods Of Measuring Icpsupporting
confidence: 71%
“…Precision wise, there is not a great difference between these two techniques, despite the fact that most microtransducers cannot be recalibrated. However, in this context it is important to point out that the Camino MicroSensor has problems with a large zero drift [74, 75]. Economically, microtransducers are more expensive, but apparently they carry a lower rate of postoperative infections.…”
Section: Discussionmentioning
confidence: 99%
“…While the Edward’s fluid sensor is extensively used for monitoring of fluid-pressures in general, including arterial blood pressure, intraventricular pressure and central venous pressure, dedicated ICP sensors were represented by the solid Codman ICP sensor [24-28], the air-pouch Spiegelberg ICP sensor [29,30], and the fibreoptic Camino ICP sensor [31,32]. …”
Section: Discussionmentioning
confidence: 99%
“…11 Microtransducers cannot be generally re-zeroed after insertion and considerable zero drift can sometimes occur in long term monitoring. 12 This problem has been addressed in the balloon-like Spiegelberg transducer which may zero itself every set time interval, although its limited bandwidth may make most of the methods used for the ICP waveform analysis impossible. 13 Contemporary epidural sensors are much more reliable than 10 years ago.…”
Section: Methods Of Measurementmentioning
confidence: 99%